An Analysis of the Customer Satisfaction from Service Quality of Himalaya Airlines - Jamkatelsh, Bishnu Prasad (International Journal of Social Sciences and Management, 2018)
The main objective of the study was to find out customer satisfaction of Himalaya airlines and analyzed the factors affecting customer satisfaction level. One hundred structured closed ended questionnaires were developed and distributed among the passengers who travelled through Himalaya airlines at Tribhuvan International airport (Kathmandu, Nepal) to collect data for result. In order to examine the effect, customer satisfaction was taken as dependent variable and ticket fares, airport services, employee behaviors, flight reliability and in-flight services were taken as independent variable. The users of Himalaya airlines in general were satisfied. It is suggested to the management to focus on fares in comparison with competitors. Int. J. Soc. Sc. Manage. Vol. 5, Issue-2: 69-71